2014
DOI: 10.5658/wood.2014.42.2.149
|View full text |Cite
|
Sign up to set email alerts
|

A New α-Amylase from Reticulitermes speratus KMT1

Abstract: Termites are wood pests that cause vast economic damage every year. They digest both cellulose and starch, but the enzymes for starch digestion have not been well characterized. We obtained complete amino acid sequence information on the KME1 α-amylase from Reticulitermes speratus KMT1 through analysis of total mRNA sequences. The KME1 enzyme has two α-amylase domains and is 68% identical to the α-amylase from Blattellager manica, its closest relative in the GenBank database. Some unique features of its conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A putative chitinase gene was selected using transcriptomic analysis from previous studies (Park et al, 2014) aimed at elucidating its biological function.…”
Section: Chitinase Genes Of R Speratus Kmt001mentioning
confidence: 99%
See 1 more Smart Citation
“…A putative chitinase gene was selected using transcriptomic analysis from previous studies (Park et al, 2014) aimed at elucidating its biological function.…”
Section: Chitinase Genes Of R Speratus Kmt001mentioning
confidence: 99%
“…A previous transcriptomic analysis of R. speratus KMT001 using the GS FLX System (Park et al, 2014) provided sequence information for the expressed mRNA.…”
Section: Putative Chitinases Of R Speratus Kmt001mentioning
confidence: 99%
“…Inoue et al (1997) found that R. serratus has both cellulase in their saliva whereas there is virtually no xylanase activity. Park et al (2014) found that R. serratus produces α-amylase which is commonly found in insect salivary glands (Cohen, 2004) and has been found in the saliva of other termite genera (Hewitt et al, 1974;La Fage & Nutting, 1978). Thus, if Reticulitermes foragers are detecting polysaccharides salivary fluid then starch should be detectable to the termites whereas xylan would not be detectable.…”
mentioning
confidence: 99%